Efficacy and safety of regorafenib as beyond second-line therapy in patients with metastatic colorectal cancer: an adjusted indirect meta-analysis and systematic review. (July 2020) - Wu, Yinying; Fan, Yangwei; Dong, Danfeng; Dong, Xuyuan; Hu, Yuan; Shi, Yu; Jing, Jiayu; Li, Enxiao
Background: The evidence base for optimum third-line therapy for metastatic colorectal cancer (mCRC) is not conclusive. Recent studies have demonstrated the efficacy of regorafenib as third-line therapy in mCRC. This indirect meta-analysis compared the efficacy and safety of regorafenib with other available third-line therapies for mCRC. Methods: A literature search for randomized controlled trials (RCTs) was conducted in PubMed, Embase, and Cochrane Library for studies evaluating the efficacy and safety of fruquintinib, regorafenib, TAS-102, and nintedanib as third-line therapies in patients with mCRC. Overall survival (OS) and progression-free survival (PFS) were the primary outcomes, while objective response rate (ORR) and safety were the secondary outcomes. Hazard ratio (HR) and relative risk (RR) with their respective 95% confidence interval (CI) were used for analysis of survival, clinical response, and safety data. An adjusted indirect meta-analysis with placebo as the common comparator was performed. Results: We identified eight RCTs comparing regorafenib (two studies), fruquintinib (two studies), TAS-102 (three studies), and nintedanib (one study) against placebo. The OS with regorafenib was significantly better when compared with nintedanib (HR = 0.66; 95% CI: 0.45, 0.95, p  = 0.02) but was similar to that of fruquintinib (HR = 1.01; 95% CI: 0.67, 1.52, p  = 0.94) and TAS-102 (HR = 0.97; 95% CI: 0.68, 1.38, p  = 0.88). The PFS and ORR for regorafenib were slightly better than those of TAS-102 (PFS: HR = 0.86, 95% CI: 0.54, 1.37, p  = 0.5; ORR: RR = 1.13, 95% CI: 0.11, 11.05, p  = 0.92) and nintedanib (PFS: HR = 0.68, 95% CI: 0.42, 1.10, p  = 0.12; ORR: not reported) but were lower than those for fruquintinib (PFS: HR = 1.53, 95% CI: 0.93, 2.52, p  = 0.08; ORR: RR = 0.68269, 95% CI: 0.045, 10.32, p  = 0.79). Safety analysis showed that the RR of adverse events (AEs) was lesser in patients treated with regorafenib in comparison with that in patients treated with fruquintinib, but was similar to that in patients treated with nintedanib and TAS-102. Conclusion: Regorafenib has efficacy similar to that of TAS-102 and better safety when compared with fruquintinib. Considering the mechanism of action of regorafenib, which targets multiple factors in the angiogenic pathway, it could be an ideal option for treatment in the beyond second-line setting.